POGLED NA LJUDSKI RAD I OBAVEZE KROZ PRIZMU RODNO OBILJEŽENE FRAZEOLOGIJE HRVATSKOGA I RUSKOG JEZIKA (Philological Studies, 2019)
The article discusses Croatian and Russian gender-marked idioms that describe human work and obligations in order to show how this part of phraseology reflects conceptions of work affected by gender stereotypes and the idea of gender-based working roles. Analized idioms illustrate certain gender-based differences in attitudes towards work and obligations, but also confirm that work is considered to be highly valued and appreciated part of human life regardless of these differences. Work is viewed as an activity that provides financial safety as well as a mean of self-realization, while hard work and work without adequate compensation has a distinctive negative connotation.
Keywords: gender-marked phraseology, work, obligation, gender stereotypes, gender-based roles, Croatian language, Russian language